Chain Whispering Games: The Effective Methods of Developing Receptive Language Skills of Children Aged 5 - 6 Years - Juniati, Ratih; Amal, Azizah; Syamsuardi, Syamsuardi (Jurnal Pendidikan Anak, 2022)
This research examines the Whispering Chain Game on Receptive Language Skills of 5-6-year-old Children in Kindergartens in Makassar City. The purpose of this study was to determine the description of children's receptive language skills before being treated, to find out the description of children's receptive language skills after being treated, and to determine whether or not there was an effect of the chain-whisper game on the receptive language skills of children aged 5-6 years in kindergarten. Makassar city before and after the chain whispering activity was given. The research approach used was a quantitative approach with a Quasi-Experimental Design type of research. The population in this study were students aged 5-6 years in TK Aisyiyah Parangtambung. Sampling in this study is cluster random sampling. The sample in this study was 12 children. A total of 6 children in the experimental group and 6 children in the control group. Data collection techniques used were descriptive statistical analysis and non-parametric statistical analysis. Based on the results of the study, it can be concluded that the receptive language skills of children who were treated with the whisper-chain game method in the experimental class were better than in the control class, while Tcount = 87 > Ttable = 2,228 was accepted, and H0 was rejected while Zcount was = 2.36 and Ztable = 0.4906 was rejected. H1 accepts this proves that the whisper-chain game method has a significant effect on receptive language skills in early childhood.